A severe presentation of acute generalized exanthematous pustulosis with non‐infectious circulatory shock in an adolescent. Issue 5 (16th July 2021) - O'Brian, Madeleine; Kolitz, Elysha; Jeong, Haneol S.; Cao, Lauren; Vandergriff, Travis; Glass, Donald A.; Dominguez, Arturo R.
Abstract: We present a severe case of acute generalized exanthematous pustulosis (AGEP) secondary to trimethoprim‐sulfamethoxazole complicated by non‐infectious circulatory shock in a 16‐year‐old boy. Hemodynamic instability has been reported as a complication of AGEP in adults, but is rarely observed in pediatric patients. The patient we present demonstrated characteristic cutaneous findings of AGEP including isolated non‐follicular, sterile pustules on a background of erythema with involvement at intertriginous areas and subsequently developed non‐infectious circulatory shock. This case expands the spectrum of possible clinical presentations for AGEP in pediatric patients.